Analysis of Lexical and Contextual Meaning in Raef’s Song Lyric of the Path Album as the Holy Qur’an Values - Risalatul Hasanah; Mosleh Habibullah (Institut Agama Islam Negeri Madura, 2020)
The Holy Qur’an is guidance to live, some of its meaning can be inserted into the lyric of the song, such as Raef’s song lyrics. Three research focuses are proposed, i.e how are the lexical meaning, how are the contextual meanings, and what are the Holy Qur’an values consists of Raef’s song lyric in The Path album. This study is a library. The data sources are Raef’s song lyric of The Path album which consists of 12 lyrics of songs, and the Holy Qur'an values. The finding revealed that in the lexical analysis, the meaning of a word is varied, for example, the keyword of